Socio-Cultural Aspects of Psychoactive Substance Use in Adolescents - Gorica Vuksanović; Olivera Kalajdžić; Ivana Zečević (Društvene i Humanističke Studije, 2023)
The use of psychoactive substances by adolescents is one of the more serious problems of modern society. Socio-cultural context plays a significant role in influencing the form of psychoactive substance use. The aim is to show the most important sociocultural factors for psychoactive substance use among adolescence, as well as a show and analysis of studies on the use of psychoactive substance use in adolescents about cultural, racial, and ethnic affiliation. Identified factors that belong to the category of sociocultural determinants are the quality of family relationships and dynamics; peer pressure; part of the city or other place where young people live, stay and/or go to school; social norms, expectations, and beliefs; legal regulations, and the general characteristics of the society. In the analyzed studies, alcohol is the most used substance among adolescents, and marijuana is the most used illegal psychoactive substance. Male adolescents are more likely to use psychoactive substances, than girls. A high prevalence of the use of psychoactive substances was registered among American Indian adolescents and young people in Colombia, while a low prevalence was recorded in Asian countries. Patterns of drug use among youth were analyzed in several tribes living in India, Thailand, and the United States. Tobacco, alcohol, and opium are the most used substance in members of these tribes.